Observations on Lepidopteran Leaf-Shelters as Molting Refuges for the Stink Bug Elasmucha Putoni (Heteroptera: Acanthosomatidae) - Shin-Ichi Kudo (Psyche: A Journal of Entomology)
When molting to the adult, the acanthosomatid bug Elasmucha putoni form aggregations on the wild mulberry Morus bombycis. The 5th-instar nymphs and/or newly molted adults were found more often in leaves rolled, folded, or tied by tortricid larvae than on unmodified leaves. Bugs probably seek protection in lepidopteran leaf-shelters during molting.